Toyama Now '84 : A New Map of A New Art. - Toyama Now '84 (Toyama : Museum of Modern Art, 1984)
Broodthaers, Marcel ; Dibbets, Jan ; Schoonhoven, Jan J. ; David Christian, Abraham ; Graubner, Gerhard ; Horn, Rebecca ; Klauke, Jürgen ; Muensch, Horst ; Richter, Gerhard ; Breivik, Bard ; Gernes, Poul ; Ultvedt, Per Olof ; Koshimizu, Susumu ; Suga, Kishio ; etc.
Toyama Now '84 : A New Map of A New Art, The Museum of Modern Art, Toyama, July 4 - September 2, 1984
Text English-Japanese
kunstcatalogus